1999
DOI: 10.1149/1.1391952
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrochemical Characterization of Glassy Carbon Prepared from Silicon‐Doped Polymethacrylonitrile/Divinylbenzene Copolymer

Abstract: Recently, the formation of lithium graphite intercalation compounds (GICs) using turbostratic (random stacking) carbon has attracted considerable attention because significantly higher intercalation levels (compared to ordered graphite compounds) have been claimed, ranging up to the composition LiC 2 . 1 Furthermore, intercalation into these materials is associated with virtually no change in layer spacing, resulting in better reversibility. Because of these favorable properties, turbostratic and disordered ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Similarly, Hayes et al [70] reported formation of Si/C composites from polymethacrylonitrile/divinylbenzene (PMAN/DVB) copolymer as a carbon precursor and tetramethylsilane (TMS) or tetravinylsilane (TVS) as Si precursor. These were mixed to form an emulsion which was polymerized at 65 • C, thermally stabilized in air at 240 • C, and finally pyrolyzed at 700 • C. The resulting material was found to have large oxygen content (22.5 wt%), negligible nitrogen content (2.99 wt%), and 10 wt% Si.…”
Section: Si/c Composite Anodes Prepared By Pyrolysis Reactions or Tvdmentioning
confidence: 99%
“…Similarly, Hayes et al [70] reported formation of Si/C composites from polymethacrylonitrile/divinylbenzene (PMAN/DVB) copolymer as a carbon precursor and tetramethylsilane (TMS) or tetravinylsilane (TVS) as Si precursor. These were mixed to form an emulsion which was polymerized at 65 • C, thermally stabilized in air at 240 • C, and finally pyrolyzed at 700 • C. The resulting material was found to have large oxygen content (22.5 wt%), negligible nitrogen content (2.99 wt%), and 10 wt% Si.…”
Section: Si/c Composite Anodes Prepared By Pyrolysis Reactions or Tvdmentioning
confidence: 99%
“…The improved performance is attributed to the coated amorphous carbon which enhanced high electrical conductivity and can buffer volume change and the agglomeration of Si nanoparticles. Hayes et al 85 86 prepared Si/C composite by ball milling graphite and crystalline Si in different atomic ratios for 150 h, then mixed the powder with colloidal polytetrafluoroethylene (PTFE) in anhydrous alcohol to prepare the anodes. The Si nanoparticles together with the graphite were encapsulated in amorphous carbon.…”
Section: Si/c Composite Anodesmentioning
confidence: 99%